2018
DOI: 10.4269/ajtmh.18-0294
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the 18-Month Cumulative Incidence of Seroconversion of Active Infection with Taenia solium Cysticercosis: A Cohort Study among Residents of 60 Villages in Burkina Faso

Abstract: Abstract.Taeniasis/cysticercosis (CC) is an important disease complex with significant burden. This large-scale cohort study aimed at estimating and exploring individual- and village-level factors associated with the cumulative incidences of seroconversion (SC) and seroreversion (SR) of active human CC in three provinces of Burkina Faso. In 60 villages, blood samples were collected and interviews regarding sociodemographic variables and knowledge, attitude, and practices toward the disease complex were conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
(45 reference statements)
2
12
1
Order By: Relevance
“…free roaming, feeding wastes, drinking free water, among others). These findings contrast with those reported in other studies in Latin America and other geographical settings, in which human cysticercosis has been associated with owning pigs [ 2 , 33 , 52 ]. Some farming practices, such as using waste or water and mix concentrate as feed, and the lack of drainage systems were non-significantly associated with increased seropositivity.…”
Section: Discussioncontrasting
confidence: 99%
“…free roaming, feeding wastes, drinking free water, among others). These findings contrast with those reported in other studies in Latin America and other geographical settings, in which human cysticercosis has been associated with owning pigs [ 2 , 33 , 52 ]. Some farming practices, such as using waste or water and mix concentrate as feed, and the lack of drainage systems were non-significantly associated with increased seropositivity.…”
Section: Discussioncontrasting
confidence: 99%
“…Our infection loss rates for HTT indicate that the duration of adult tapeworm infection (the reciprocal of ρinf) ranges from 1.3 to 1.4 years (with uncertainty bounds from 1.0 to 2.8 years), aligning with literature estimates suggesting that adult tapeworms live for less than 5 years (Garcia et al, 2014), although our values are only based on two studies. HCC Ab-seroreversion rates (or infection loss rates) from this analysis are also consistently larger than HCC Ab-seroconversion rates (or infection acquisition rates), in agreement with comparisons of HCC Ab-seroreversion to Abseroconversion (or Ag-seroreversion to Ag-seroconversion) estimates in the literature, which are (Dermauw et al, 2018;Garcia et al, 2001;Coral-Almeida et al, 2015;Mwape et al, 2013). Some of the modelled estimates presented here indicate large differences between FoI and Abseroreversion/infection loss rates.…”
Section: Discussionsupporting
confidence: 87%
“…The results from this model become very useful in elucidating the observed effectiveness of the educational intervention tested as part of the clustered randomized controlled trial conducted in these villages. The trial showed that the intervention was most effective in Sanguié and Nayala, but not in Boulkiemdé [ 23 ]. The model suggested that more intensive improvements in latrine use and pork cooking habits were needed in Boulkiemdé than in Nayala and Sanguié to eliminate the infection ( Fig 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in sanitation were assumed to be associated with behavioral changes in response to the education intervention used in the cluster randomized controlled trial of the parent study [ 23 ]. Improved sanitation was expected to reduce the rate of transmission associated with human exposure to T .…”
Section: Methodsmentioning
confidence: 99%